Multimodal MRI-based radiomics in an ASD rat model: investigating brain structural changes and the neuroprotective effects of selenium - Shu, Yikai; Zhang, Xiaoan; Huang, Jun; Li, Chengdong; Zhang, Yang (Frontiers in Neuroscience, 2025)
IntroductionThis study developed and validated a multimodal MRI-based radiomics model to assess brain changes in a rat model of autism spectrum disorder (ASD) following selenium intervention.MethodsASD was induced in Sprague–Dawley rats via prenatal valproic acid administration, with sodium selenite used for intervention. MRI modalities included T2-weighted imaging, T1 and T2 relaxation mapping, diffusion tensor imaging, and diffusion kurtosis imaging. Radiomics features were extracted, correlated with behavioral metrics, and analyzed using clustering and radiomics scoring. Logistic regression models incorporating single-modality and multimodal radiomics features were developed and evaluated using receiver operating characteristic (ROC) curve analysis. Subgroup analyses assessed predictive performance and correlations with behavioral and developmental indices.ResultsASD model rats exhibited growth retardation, anxiety-like behavior, and deficits in social interaction and memory, which were alleviated by selenium supplementation. The multimodal radiomics model outperformed single-modality models, achieving the highest area under the ROC curve and strong predictive capability in subgroup analyses. Significant correlations were identified between multimodal radiomics scores and behavioral as well as developmental measures.DiscussionThe cerebellum was a key region affected in ASD, whereas the visual–auditory cortex showed notable responses to selenium treatment. In conclusion, the multimodal radiomics model demonstrates high diagnostic efficacy, highlights the cerebellum as a key region affected in ASD, and suggests the visual–auditory cortex as a primary target of selenium intervention, enhancing predictive accuracy for structural and functional brain improvements post-treatment.